The X Family Portrait: Structural Insights into Biological Functions of X Family Polymerases - Moon, Andrea F. (2007)
The mammalian Family X DNA polymerases (DNA polymerases β, λ, μ, and TdT) contribute to base excision repair and double-strand break repair by virtue of their ability to fill short gaps in DNA. Structural information now exists for all four of these enzymes, making this the first mammalian polymerase family whose structural portrait is complete. Here we consider how distinctive structural features of these enzymes contribute to their biological functions in vivo.